The Evolution of Distributed Computing in E-commerce and SaaS Platforms - Bala Srinivas Pillarisetty, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Distributed computing has fundamentally transformed the architecture and capabilities of modern e-commerce and SaaS platforms, enabling unprecedented scale, resilience, and performance. This transformative paradigm distributes computational tasks across interconnected nodes, allowing systems to maintain exceptional uptime and transaction processing capabilities even during extreme load conditions. Organizations implementing distributed architectures experience significant improvements in system reliability and substantial reductions in downtime compared to traditional monolithic systems. The economic impact is considerable—with distributed systems preserving substantial annual revenue through enhanced availability during peak traffic periods. Key architectural approaches, including event-driven design, microservices, and distributed databases, form the foundation for performance-critical applications across digital commerce. These patterns enable real-time inventory synchronization, dynamic pricing adjustments, personalized recommendations, and fraud detection at a scale previously unattainable. Despite delivering tremendous benefits, distributed systems introduce complexity challenges around consistency tradeoffs, transactions across service boundaries, observability requirements, network latency management, and expanded security considerations. Emerging trends, including serverless computing, edge processing, AI-driven orchestration, service mesh networks, and quantum-resistant cryptography, promise to address current limitations while introducing powerful new capabilities for the next generation of distributed platforms.
Keywords: Distributed Computing; Microservices Architecture; Event-Driven Systems; Multi-Tenancy Models; Edge Computing